We come to life with those we serve - Gunderman, Richard B. (Indiana University Press, 2017)
What is the most meaningful and rewarding path in life? The legendary, real-life individuals and famous literary characters in this inspiring book show us the way. Gunderman persuasively argues that, far from draining away ourvitality, service at its best brings us to life.